Croatian Immigrants’ Language Use and Attitudes: The Case of Croatian, English, and Swedish in Sweden - Škifić, Sanja (Slavia Centralis, 2022)
This paper deals with the analysis of language use and attitudes related to Croatian, English, and Swedish among Croatian immigrants in Sweden. The research was conducted during October and November 2020, and it included 64 Croatian immigrants in Sweden. The questionnaire that was used in the research was modelled on the questionnaire used by Škifić and Grbas (2020) in their research on language use and attitudes among Croatian immigrants in Ireland. The results of the research point to respondents’ positive attitudes towards residing in Sweden, as well as their attitudes regarding the greater importance of the knowledge of Swedish than English. The respondents’ current level of the knowledge of the English language has been evaluated higher than their current level of knowledge of the Swedish language, while a more significant progress in the knowledge of the two languages has been noted in the case of Swedish. Different domains of language use have been shown to be relevant in identifying the dominant use of Croatian, English and Swedish, while both the knowledge of Swedish and the knowledge of English have been noted as important for employment.